2019
DOI: 10.1097/ico.0000000000001923
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Biofilm Plaques: A Novel Clinical Presentation

Abstract: Purpose: To report a novel clinical presentation of corneal biofilms, consisting of formation of superficial and recurrent corneal plaques. Methods: Interventional case report. A 9-year-old boy presented with subepithelial, whitish, avascular, and recurrent corneal plaques without any clinical manifestations of active corneal inflammation and/or infection. He had a history of minor ocular trauma; otherwise, his medical history was unremarkable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…[ 25 , 62 , 63 , 90 ], to understand their biofilm formation ability on indwelling devices including contact lenses, sutures, scleral buckles, valvular tubes and keratoprostheses [ 20 , 24 , 25 , 26 , 52 , 77 , 91 , 92 , 93 ]. In our opinion, monitoring biofilm formation of ocular fluid S. aureus and S. epidermidis on cadaveric cornea is equally important because they are a major source of hospital-acquired infections and more importantly, corneal biofilms have been reported following experimental keratitis in mice [ 77 ], in patients with infectious crystalline keratopathy [ 94 , 95 , 96 ] or pterygium scleritis [ 97 ] and also in the absence of prosthetic material and in the absence of active corneal inflammation or infection [ 59 ]. Comparison of the biofilms formed on cover slips with that of cadaveric cornea indicated that EPS secretion was more copious on cornea ( Figure 5 and Figure 6 ) than on cover slip ( Figure 3 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25 , 62 , 63 , 90 ], to understand their biofilm formation ability on indwelling devices including contact lenses, sutures, scleral buckles, valvular tubes and keratoprostheses [ 20 , 24 , 25 , 26 , 52 , 77 , 91 , 92 , 93 ]. In our opinion, monitoring biofilm formation of ocular fluid S. aureus and S. epidermidis on cadaveric cornea is equally important because they are a major source of hospital-acquired infections and more importantly, corneal biofilms have been reported following experimental keratitis in mice [ 77 ], in patients with infectious crystalline keratopathy [ 94 , 95 , 96 ] or pterygium scleritis [ 97 ] and also in the absence of prosthetic material and in the absence of active corneal inflammation or infection [ 59 ]. Comparison of the biofilms formed on cover slips with that of cadaveric cornea indicated that EPS secretion was more copious on cornea ( Figure 5 and Figure 6 ) than on cover slip ( Figure 3 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…A unique feature of this study is that in addition to using cover slips, human donor corneas were also used as a substratum for monitoring biofilm formation. This approach of using cadaveric cornea as a substratum is important since bacteria colonize the cornea, allow prolonged survival of microorganisms and are the cause of active inflammation and infection [ 59 ]. Further, antibiotic susceptibility was monitored both in the planktonic and biofilm phases.…”
Section: Introductionmentioning
confidence: 99%
“…A previously unknown clinical presentation of a corneal biofilm, consisting of superficial and recurrent corneal plaques, has recently been reported, which allows the prolonged survival of microorganisms even in the absence of prosthetic material, clinical signs, or symptoms of active corneal inflammation and/or infection [48]. It seems that bacteria can persist for long periods inside this structure, and thus create probably low-grade inflammation similar to that which occurs in the case of a typical biofilm-related infection [49].…”
Section: Role Of Biofilm In Eye Infectionsmentioning
confidence: 99%